Noin suuri - Ferber, Edna, 1885-1968; Soini, Elsa, 1893-1952 (Salt Lake City, UT : Project Gutenberg, 2025)
"Noin suuri : Romaani by Edna Ferber" is a novel written in 1924. The story follows Selina Peake De Jong, a school teacher who marries a Dutch farmer and raises their son Dirk in farming country. When her husband dies, Selina works the farm alone to provide for her son's future. As Dirk grows up, he chooses financial success over artistic integrity, disappointing his mother who has always valued beauty and aesthetics. The novel won the Pulitzer Prize in 1925. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/So_Big_(novel)
Release date is 2025-10-23
Tuula Temonen
Keywords: Domestic fiction; Fathers and daughters -- Fiction; Bildungsromans; Chicago (Ill.) -- Fiction; Gamblers -- Family relationships -- Fiction